2020
DOI: 10.55230/mabjournal.v49i1.1663
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL SCREENING, ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF EXTRACTS AND FRACTIONS OF Dillenia suffruticosa LEAVES

Abstract: Dillenia suffruticosa or ‘Simpur bini’ is known to have ethnomedicinal properties and had been used traditionally to heal wounds, relieve fever and rheumatism. There has been limited studies carried out on this species, therefore, this study aims to evaluate the phytochemical contents, antioxidant and antibacterial activities of aqueous extract, methanol extract and its fractions obtained from the leaves of D. suffruticosa. The dried leaves were extracted using methanol before successive solvent partitioning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Methanol extract of stem bark of D. serrata scavenged DPPH radicals (48.2-59.7%) at 100 μg/mL (Sabandar et al 2020). Methanol extract D. suffruticosa leaves has IC50 305.09±4.53 μg/mL DPPH radical scavenging (Yakop et al 2020;Sinala et al 2020). This study used ascorbic acid as a comparison (Table 5).…”
Section: Antioxidant Activity Dpph Methods (22-diphenyl-1-picrylhydra...mentioning
confidence: 99%
See 4 more Smart Citations
“…Methanol extract of stem bark of D. serrata scavenged DPPH radicals (48.2-59.7%) at 100 μg/mL (Sabandar et al 2020). Methanol extract D. suffruticosa leaves has IC50 305.09±4.53 μg/mL DPPH radical scavenging (Yakop et al 2020;Sinala et al 2020). This study used ascorbic acid as a comparison (Table 5).…”
Section: Antioxidant Activity Dpph Methods (22-diphenyl-1-picrylhydra...mentioning
confidence: 99%
“…Based on the results obtained, the extract's yield is large. Bordoloi et al 2019 reported that ethanolic extract of D. indica has a 4.7% yield, 10.07% of methanol extract of fruit (Gogoi et al 2012), and 21.8% in methanolic extract of D. suffruticosa leaves (Yakop et al 2020).…”
Section: Phytochemical Testmentioning
confidence: 99%
See 3 more Smart Citations